2014
DOI: 10.1371/journal.pone.0098183
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Treatment Outcomes for HIV-1 and HIV-2-Infected Adults Enrolled in Côte d'Ivoire's National Antiretroviral Therapy Program

Abstract: BackgroundIn Côte d'Ivoire during 2004–2007, numbers of ART enrollees increased from <5,000 to 36,943. Trends in nationally representative ART program outcomes have not yet been reported.Methodology/Principal FindingsWe conducted a retrospective chart review to assess trends in patient characteristics and attrition [death or loss to follow-up (LTFU)] over time, among a nationally representative sample of 3,682 adults (≥15 years) initiating ART during 2004–2007 at 34 health facilities. Among ART enrollees durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
3
24
0
Order By: Relevance
“…Decroo et al reported high retention with approximately 97.5% patients remaining in care for a median follow-up period of 12.9 months (range 8.5–14 months) 16 and 91.8% at 4 years. 17 Overall, the authors reported that attrition in the cohort was lower than the national 12 month average for Mozambique (15%) 28 and lower still than rates reported in the literature for sub-Saharan Africa (1.2–26%). 29 A large study with more than 300,000 participants aged 10–24 years from four sub-Saharan countries showed that youth participating in support groups provided by clinics experienced slightly lower attrition after ART initiation (AHR=0.73, 95% CI: 0.52–1.0); in the pre-ART period, the authors reported no significant associations between attrition and participation in support groups or other adolescent friendly services—availability of adolescent peer educators, or education on high-risk substance abusing behaviour.…”
Section: Resultsmentioning
confidence: 78%
“…Decroo et al reported high retention with approximately 97.5% patients remaining in care for a median follow-up period of 12.9 months (range 8.5–14 months) 16 and 91.8% at 4 years. 17 Overall, the authors reported that attrition in the cohort was lower than the national 12 month average for Mozambique (15%) 28 and lower still than rates reported in the literature for sub-Saharan Africa (1.2–26%). 29 A large study with more than 300,000 participants aged 10–24 years from four sub-Saharan countries showed that youth participating in support groups provided by clinics experienced slightly lower attrition after ART initiation (AHR=0.73, 95% CI: 0.52–1.0); in the pre-ART period, the authors reported no significant associations between attrition and participation in support groups or other adolescent friendly services—availability of adolescent peer educators, or education on high-risk substance abusing behaviour.…”
Section: Resultsmentioning
confidence: 78%
“…As described earlier, because cohorts R and B do not overlap during the stepped-wedge portion of this trial, a comparison of 6-month mortality rates in cohorts R and B cannot make use of the stepped-wedge design to control for secular trends [26]. However, since most variation in 6-month ART mortality over successive annual ART cohorts is accounted for by changes in health status of ART enrollees (e.g., changes in baseline CD4 count), incorporation of these known risk factors for 6-month ART mortality into the multivariable model may fully account for secular mortality trends [7, 50]. …”
Section: Methodsmentioning
confidence: 99%
“…Healthcare facility-related reasons for missed or late TB diagnoses among PLHIV include: (1) failure of healthcare workers (HCW) to screen for TB symptoms [79]), (2) failure of HCWs to request sputum or other diagnostic samples from symptomatic patients [10], (3) inability to collect high quality sputa or other appropriate diagnostic samples from symptomatic patients [11], (4) insensitive TB diagnostics, with smear microscopy alone having a sensitivity of about 45 % in diagnosing culture-positive disease among PLHIV [12], (5) inability to diagnose drug-resistant TB timeously [13], and (6) long turn-around times for some TB diagnostic tests or failure to return results to clinicians and patients [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Because such system strengthening is a long-term endeavor, complimentary data collection exercises help to meet immediate information needs for HIV program information. [64][65][66] …”
Section: The Current State Of Global Hiv Mandementioning
confidence: 99%